Foot progression angle in relation to spatiotemporal parameters of gait in children with cerebral palsy - Hisham Mohamed Elsawy; Elham El-sayed SalemDr; Asmaa Osama Sayed; Sherif Naseef Girgis (2025)
The purposes of this study were to assess the difference in the foot progression angle (FPA) and measure spatiotemporal parameters of gait among the three age groups (from five to six, more than six to seven, and more than seven to eight years) of diplegic cerebral palsied children and to investigate the relation between FPA of the right and left lower extremities and spatiotemporal parameters of gait in diplegic cerebral palsied children. Sixty spastic diplegic cerebral palsied children with ages ranging from 5 to 8 years participated in this study. They were classified into three age groups of equal numbers: group (A); from 5 to 6 years; group (B); more than 6 to 7 years; and group (C); more than 7 to 8 years. Both feet progression angles were measured using a dynamic footprint. Results revealed no significant difference in the mean values of the FPA and speed among the three study groups for both right and left feet. There was a significant increase in right (step length, stride length, single support) and left (stride length, single support) between the three groups, while there was no significant difference in left step length between the three groups. Also, there was a significant decrease in cadence between the three groups. Results showed a non-significant correlation between right FPA and all spatiotemporal parameters in three groups. There was a non-significant correlation between left FPA and all spatiotemporal parameters in groups A and B. Results showed that there was a moderately negative significant correlation between left FPA and right step length, right stride length, and moderately positive significant correlation of cadence at group C. The results of the present study provide quantitative and objective information that could be used in the clinical assessment of rehabilitation strategies
(3JgOa gPg GdOQGSI gj Jbjje GdGNJdGa aj RGhjI GdbOe hbjGS hGdYGed GdecGfj GdReGfj ddeTj Hjf GdaFGJ GdYeQjI GdKdGK (B((3ef NeS Edi SJ SfhGJ, CcKQ ef SJ Edi SHY SfhGJ, h CcKQ ef SHY Edi KeGfj SfhGJ(B) (3ddCWaGd GdeUGHjf HGdTdd GdOeGZj GdeROhL, hHMK GdYdGbI Hjf GdJHGjf aj RGhjI GdbOe aj GdCWQGa GdSadjI Gdjefi hGdjSQi hGdYGed GdecGfj GdReGfj ddeTj dOi GdCWaGd GdeUGHjf HGdTdd GdOeGZj GdeROhL(B. (3TGQc aj gPg GdOQGSI SJhf WadkG eUGHkG HGdTdd GdOeGZj GdeROhL JJQGhM CYeGQge Hjf (B5 (3h(B8 (3SfhGJ(B. (3Je JUfjage Edi KdGK eLehYGJ YeQjI eJSGhjI GdCYOGO(B: (3GdeLehYI (B((3C(B) (3ef (B5 (3Edi (B6 (3SfhGJ, hGdeLehYI (B((3H(B) (3CcKQ ef (B6 (3Edi (B7 (3SfhGJ, hGdeLehYI (B((3L(B) (3CcKQ ef (B7 (3Edi (B8 (3SfhGJ(B. (3Je bjGS RGhjI GdbOe dcdG GdbOejf HGSJNOGe GdHUeI GdOjfGejcjI(B. (3cTaJ GdfJGFL Yf YOe hLhO GNJdGa cHjQ Gdbje GdeJhSWI dRGhjI GdbOe ddbOejf hGdSQYI Hjf eLehYGJ GdOQGSI GdKdGK dcd ef GdbOejf Gdjefi hGdjSQi(B. (3cGf gfGc RjGOI cHjQI aj GdbOe Gdjefi (B((3Whd GdNWhI, hWhd GdNWhI GdeROhL, hGdGQJcGR Ydi bOe hGMO(B) (3hGdbOe GdjSQi (B((3Whd GdNWhI, hGdGQJcGR Ydi bOe hGMO(B) (3Hjf GdeLehYGJ GdKdGK, HjfeG de jcf gfGc aQb cHjQ aj Whd GdNWhI GdjSQi Hjf GdeLehYGJ GdKdGK(B. (3ceG cGf gfGc GfNaGV cHjQ aj GdEjbGY Hjf GdeLehYGJ GdKdGK(B. (3CXgQJ GdfJGFL hLhO YdGbI djSJ PGJ OdGdI EMUGFjI Hjf RGhjI GdbOe GdCjef hGdYGed GdecGfj GdReGfj aj GdeLehYGJ GdKdGK(B. (3cGf gfGc YOe eYfhjI hLhO GQJHGW Hjf RGhjI GdbOe GdCjef hGdYGed GdecGfj GdReGfj aj GdeLehYJjf (B((3C(B) (3h (B((3H(B). (3CXgQJ GdfJGFL hLhO YdGbI GQJHGW eYfhj SdHj eYJOd Hjf RGhjI GdbOe GdYVdj GdCjef hGdYGed GdecGfj GdReGfj aj GdeLehYGJ GdKdGK(B. (3cGf gfGc GQJHGW djS Pj OdGdI EMUGFjI Hjf RGhjI GdbOe GdjSQi hGdYGed GdecGfj GdReGfj aj GdeLehYJjf (B((3C(B) (3h(B((3H(B). (3CXgQJ GdfJGFL hLhO GQJHGW eYfhj SdHj eYJOd Hjf RGhjI GdbOe GdjSQi hWhd GdNWhI Gdjefi hWhd GdNWhI GdeROhL Gdjefi hGQJHGW eYfhj EjLGHj eYJOd ddEjbGY aj GdeLehYI (B((3L(B). (3JhaQ fJGFL gPg GdOQGSI eYdheGJ cejI hehVhYjI jecf GSJNOGegG aj GdJbjje GdSQjQj dGSJQGJjLjGJ EYGOI GdJCgjd ddcTa Yf GdJThgGJ GdhXjajI hJMOjO GdYdGL GdefGSH(B. s
Thesis (Ph.D)-Cairo University, 2025.
Bibliography: pages 73-89.
Issues also as CD.
Text in English and abstract in Arabic & English.
Keywords: Physical Therapy; (3GdYdGL GdWHjYj s; Foot progression angle -- Spatiotemporal, -- Dynamic footprint -- cerebral palsy -- diplegia